2011
DOI: 10.1021/jf200017h
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Essential Oil Composition within Individual Leaves of Sweet Basil (Ocimum basilicum L.) Is More Affected by Leaf Position than by Leaf Age

Abstract: The aroma in sweet basil is a factor affecting the commercial value of the crop. In previous studies leaf age was considered to be a factor that influences the composition of essential oil (EO). In this study it was hypothesized that a single observation of the EO content in leaves from different positions on the main stem (young vs old) could predict the developmental changes in the plant during its life cycle. Plants harvested at week 16 demonstrated an exponential increase (R(2) = 0.92) in EO concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Likewise, an opposite trend was observed in relative abundances of GARD B and pebrellin, a potential precursor of GARD B lacking only the 6-O-methyl group, which was attributed to changes in the expression of a F6OMT (Voirin and Bayet, 1992). This observation is in line with previous studies on terpene composition in basil (Johnson et al, 1999), peppermint (Brun et al, 1991), and thyme (Thymus vulgare; Yamaura et al, 1992) but contrasts with recent findings (Fischer et al, 2011) that the relative concentrations of several essential oil components in basil are strongly predetermined by the leaf position and vary little throughout leaf development.…”
Section: Line-specific Profiles Of External Flavones Are Conserved Thsupporting
confidence: 71%
“…Likewise, an opposite trend was observed in relative abundances of GARD B and pebrellin, a potential precursor of GARD B lacking only the 6-O-methyl group, which was attributed to changes in the expression of a F6OMT (Voirin and Bayet, 1992). This observation is in line with previous studies on terpene composition in basil (Johnson et al, 1999), peppermint (Brun et al, 1991), and thyme (Thymus vulgare; Yamaura et al, 1992) but contrasts with recent findings (Fischer et al, 2011) that the relative concentrations of several essential oil components in basil are strongly predetermined by the leaf position and vary little throughout leaf development.…”
Section: Line-specific Profiles Of External Flavones Are Conserved Thsupporting
confidence: 71%
“…The lowest values of phenolic content were found in in vitro root, although this part contained almost twice as much eugenol compared to field grown roots. The diversity of the aromatic compounds in the leaves was affected significantly by the ageing of the leaf or the process of maturation (Fischer, Nitzan, Chaimovitsh, Rubin, & Dudai, 2011), and methylating enzymes (eugenol-O-methyltransferase and chavicol-O-methyltransferase) play a major role in the diversity and distribution of phenyl propene compounds (Lewinsohn et al, 2000), which could be the reason for the diverse eugenol content in the various analysed parts of the plant. A recent study demonstrated that some of the secondary metabolites detected in rapeseed have also different tissue-specific distribution patterns.…”
Section: Relationship Between Eugenol and Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Freshly removed inflorescences (150 g/plot) were dissected into 1 cm long sections and were submitted to hydro-distillation in a Clevenger-type apparatus for 1.5 h. The essential oil composition was analyzed using the GC-MS procedure (Fischer et al 2011). …”
Section: Essential Oil Extractionmentioning
confidence: 99%